Occupational respiratory symptoms and associated factors among street sweepers in low- and middle-income countries: A systematic review and meta-analysis. - Belay Desye; Abebe Kassa Geto; Leykun Berhanu; Chala Daba; Gete Berihun (PLoS ONE)
In low- and middle-income countries, occupational exposure continues to be a serious public health concern. Because of their working conditions, street sweepers are particularly vulnerable to health hazards, with respiratory issues being the most common. The lack of comprehensive and inconsistence evidence on occupational respiratory symptoms among street sweepers, which exacerbates this issue. This study aimed to estimate the pooled prevalence of occupational respiratory symptoms and associated factors among street sweepers in low- and middle-income countries. A comprehensive search strategy was carried out using various databases, such as PubMed, Scientific Direct, HINARI and Google Scholar, and the grey literature. The preferred reporting items for systematic reviews and meta-analyses were used. Microsoft Excel was used to extract the data, which was then transferred to STATA 14/SE software for analysis. The Joanna Briggs Institutes' quality appraisal tool was used to ensure the quality of the included articles. A random effects model was used to estimate the pooled prevalence. In this study, a subgroup analysis was employed to examine the potential sources of heterogeneity, and sensitivity analysis was conducted to assess the effect of individual studies on the pooled results. To evaluate publication bias, the funnel plot and Egger's regression tests were employed. The pooled prevalence of occupational respiratory symptoms among street sweepers was estimated to be 47.35% (95% CI: 34.59-60.11). Among each respiratory symptom, cough was found to be the most prevalent at 38.37% (95% CI: 28.54-48.19). In this study, past dust exposure (OR = 2.84, 95% CI: 1.06-4.61), not using facemasks (OR = 2.67, 95% CI: 1.54-3.81), having more than five years of work experience (OR = 3.68, 95% CI: 1.66-5.7), and being between the ages of 38 and 47 (OR = 2.17, 95% CI: 1.07-3.27) were found to be predictor factors with occupational respiratory symptoms among street sweepers. Furthermore, there is no evidence of publication bias for this study. The findings of this study indicated a significant prevalence of occupational respiratory symptoms among street sweepers. Therefore, it is highly recommended to focus on the provision and proper use of personal protective equipment and to enhance occupational health and safety training.